Development of Preschool Children’s Speech Based on the Asyk Methodological and Technological Approach (Journal of Educational Sciences, 2025)
This article examines the integration of national play elements with modern methodological and technological approaches in developing the speech of preschool children. The study was conducted at the State Kindergarten No.187 located in the Turksyb District of Almaty city. 60 children took part in the experiment. The new approach the «Asyk Methodological Technology» was adapted for speech therapy sessions and aimed not only at improving articulatory movements but also at enhancing fine and gross motor skills, cognitive activity, attention, memory, and spatial orientation. The technology is based on the traditional Kazakh game Asyk, through which a set of articulatory, neuro-gymnastic, and bio-energo-plastic exercises were organized. The research findings indicated that the systematic use of the Asyk technology not only corrected speech disorders but also increased linguistic activity, emotional stability, and cultural identity among children. The synthesis of national content and innovative logopedic methods made this technology an effective pedagogical innovation aimed at fostering the comprehensive development of the child within the preschool education system.Keywords: Asyk technology, speech development, preschool education, speech therapy, motor coordination, neuro- gymnastics, national games.